2003
DOI: 10.1152/ajplung.00249.2002
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced neutrophilic inflammation and Bcl-2 expression in metaplastic mucous cells

Abstract: Our previous studies show that Bcl-2, a regulator of apoptosis, may be involved in the reduction of mucous cell metaplasia (MCM) during recovery from inflammatory responses. The present study was to determine whether neutrophilic inflammation mediates Bcl-2 expression in mucous cells. Rats were intratracheally instilled with 50–1,000 μg of LPS. The number of neutrophils recovered by bronchoalveolar lavage (BAL) increased with the dose of LPS, and the percentage of Bcl-2-expressing cells increased with the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 41 publications
6
26
0
1
Order By: Relevance
“…Figure 6C suggests that Bcl-2-positive cells occurred only in animals in which the neutrophil count was Ͼ10 cells/l (equivalent to 20% neutrophils), and in RAO-affected animals, the number of Bcl-2-positive cells tended to increase with severity of neutrophilic inflammation. A similar association between the number of Bcl-2-positive mucous cells and numbers of neutrophils in airways also has been reported in rats challenged with two doses of endotoxin (6). However, neutrophils are not essential for Bcl-2 expression, because, in the latter model, neutrophil depletion did not reduce the number of Bcl-2-positive cells.…”
Section: Discussionsupporting
confidence: 79%
“…Figure 6C suggests that Bcl-2-positive cells occurred only in animals in which the neutrophil count was Ͼ10 cells/l (equivalent to 20% neutrophils), and in RAO-affected animals, the number of Bcl-2-positive cells tended to increase with severity of neutrophilic inflammation. A similar association between the number of Bcl-2-positive mucous cells and numbers of neutrophils in airways also has been reported in rats challenged with two doses of endotoxin (6). However, neutrophils are not essential for Bcl-2 expression, because, in the latter model, neutrophil depletion did not reduce the number of Bcl-2-positive cells.…”
Section: Discussionsupporting
confidence: 79%
“…The onset of GCM correlates with the decline of PMN numbers as was shown in previous studies [12,6,15], and is maintained through d 6 when macrophage numbers are highest. We also observed that macrophage and PMN numbers were equal and lymphocyte numbers were maximum by d 4 when GCM is highest, suggesting that a combination of factors derived from these cell types, may be contributing to epithelial cell hyperplasia and increased mucin synthesis and storage resulting in GCM.…”
Section: Discussionsupporting
confidence: 77%
“…Notable, previous reports show that LPS exposure can upregulate Bcl-2 regardless of airway location and promote the differentiation of proliferating and preexisting epithelial cells into mucous cells [44,45] . Chronic LPS exposure may cause persistently elevated mucous cell numbers and contribute to mucous hypersecretion and airway obstruction as in chronic lung disease, such as cystic fibrosis or chronic bronchitis [44,45] .…”
Section: Discussionmentioning
confidence: 93%
“…Chronic LPS exposure may cause persistently elevated mucous cell numbers and contribute to mucous hypersecretion and airway obstruction as in chronic lung disease, such as cystic fibrosis or chronic bronchitis [44,45] . Although these previous reports and our present results appear to be contradictory, they are, in fact, two sides of the same coin.…”
Section: Discussionmentioning
confidence: 99%